2018
DOI: 10.7150/thno.26055
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of heart failure biomarkers are primarily a reflection of extracardiac production

Abstract: Plasma heart failure (HF) biomarkers, like natriuretic peptides, are important in diagnosis, prognosis and HF treatment. Several novel HF biomarkers have been identified, including Gal-3, GDF-15 and TIMP-1, but their clinical potential remains vague. Here we investigated plasma biomarker levels in relation to tissue expression and structural and functional cardiac changes.Methods: Cardiac remodeling, cardiac function, and plasma and tissue biomarker levels were investigated in mice after myocardial infarction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(92 citation statements)
references
References 49 publications
5
83
0
4
Order By: Relevance
“…This may be explained because in heart failure patients, several other organs undergo fibrotic changes as well: liver, lungs, kidneys, and vessels. A recent article by Du and colleagues showed that galectin‐3, growth differentiation factor‐15, and TIMP‐1 plasma levels do not reflect myocardial fibrosis in mouse models of post‐MI heart failure, hypertensive heart failure, and HFpEF . Instead, production in extracardiac tissues such as fatty and lung tissue had much greater impact on plasma levels of these markers.…”
Section: Improved Methods Are Needed To Detect Fibrosis Using Biomarkmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be explained because in heart failure patients, several other organs undergo fibrotic changes as well: liver, lungs, kidneys, and vessels. A recent article by Du and colleagues showed that galectin‐3, growth differentiation factor‐15, and TIMP‐1 plasma levels do not reflect myocardial fibrosis in mouse models of post‐MI heart failure, hypertensive heart failure, and HFpEF . Instead, production in extracardiac tissues such as fatty and lung tissue had much greater impact on plasma levels of these markers.…”
Section: Improved Methods Are Needed To Detect Fibrosis Using Biomarkmentioning
confidence: 99%
“…A recent article by Du and colleagues showed that galectin-3, growth differentiation factor-15, and TIMP-1 plasma levels do not reflect myocardial fibrosis in mouse models of post-MI heart failure, hypertensive heart failure, and HFpEF. 53 Instead, production in extracardiac tissues such as fatty and lung tissue had much greater impact on plasma levels of these markers. So ideally, we would need a marker that is specific for cardiac fibrosis, or at the very least, adequately reflects changes in myocardial fibrosis.…”
Section: Circulating Biomarkers Of Myocardial Fibrosismentioning
confidence: 99%
“…Based on the previous studies, plasma biomarkers can offer great promise to further dissect the underlying disease processes, which are important in diagnosis, prognosis, and HF treatment [45,46]. Thus, we attempted to investigate whether the COL1A1 content in plasma would be used as a biomarker for HF progression.…”
Section: Experimental Validation Of Col1a1 As a Potential Biomarker Imentioning
confidence: 99%
“…These data suggest that in patients with HF, after adjustment for clinical confounders, the levels of NT-proBNP, but not GDF-15, are significantly influenced by the presence of AF at time of measurement. GDF-15 is mainly produced in non-cardiac and peripheral tissues, such as endothelial cells and adipocytes, and we recently showed that the levels of GDF-15 in mice are 2-to 60-fold higher in the liver, lungs and kidney than in the cardiac muscle [19]. Therefore, this marker reflects changes in many organs, not just in the cardiac ventricles and atria, and might therefore be less likely to be load-dependent as compared with NT-proBNP.…”
Section: Discussionmentioning
confidence: 99%